Knowledge, Attitude, and Practice of Nurses Working in the Adult Intensive-Care Unit and Associated Factors towards the Use of Physical Restraint in Federally Administered Hospitals in Addis Ababa, Ethiopia: A Multicenter Cross-Sectional Study - Lielt Mersha Woldekirkos; Tilahun Jiru; Heyria Hussien; Belayneh Shetie (Critical Care Research and Practice)
Background. Physical restraint is any chemical or physical involuntary method restricting an individual’s movement, physical activity, or normal access to the body. Physical restraints are prescribed by the physician, but the ICU nurse remains the decision maker responsible in assessing the need, application, and removal of PR on patients in the ICU setting. Objectives. This cross-sectional descriptive study was carried out to determine the knowledge, attitudes, and practices of nurses working in adult ICU and associated factors towards the use of physical restraints in federally administered hospitals in Addis Ababa, Ethiopia, 2019. Methods. The study was conducted in ICUs of Federal Hospitals in Addis Ababa, Ethiopia, 2019. A hospital-based descriptive cross-sectional study design was carried out. By census, a total of 126 nurses were included. The data were checked for their completeness and were entered to EpiData version 4.2 and analyzed using SPSS version 25 software with 95% CI. Also, the Pearson correlation coefficient and binary logistic regression analysis were used to find an association. Result. Majority of nurses was found to be aged between 21 and 30 years, (62.5%) have worked 2–5 years, and (83%) were degree graduates. The nurses’ knowledge score was 6.1 ± 2.6 (50.8%) with possible range 0–11, the attitude score was 14.1 ± 3.1 (64%) with possible range 0–22, and the practice score was 13.9 ± 3.8 (63.18%) with possible range 0–22. Their demographical characteristics such as gender, working year, and education levels were not significantly associated with knowledge, attitudes, and practices (P > 0.05). Only age significantly associated with practice. Lack of a written policy or guideline and not being trained on application of physical restraint were significantly associated with knowledge. Also, practice was associated with knowledge and attitude. Conclusion. According to the study, there was a poor level of nurses’ knowledge, proper attitude, and satisfactory practice toward the use of physical restraints.